Analisis daur hidup pembangkit listrik berbasis batu bara: dampaknya terhadap jejak karbon perkotaan dan biaya eksternal - Mahroini, Zahidah; Bainirad, Feneubrina (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Indonesia’s economic growth is strongly driven by industrial activities concentrated in large urban areas, resulting in high energy demand. Approximately 40-70% of Indonesia’s energy is supplied by coal combustion, contributing significantly to carbon emissions and accelerated global warming. The coal used would still be main source in the future energy of Indonesia especially in cities. This study proposes to estimate the carbon emission and environmental cost (EC) of power plant life cycle use benefits transfer method, while also accounting air = and water pollution. The results show that during 2010-2020, the EC for GHG emission is about 9 to 19 billion US, while EC for air pollution is about 1.56-5.37 billion US. Water pollution averaged 0.002658049 g/TWh for phenol and 9.16425 g/TWh for total COD. Then, the total water depletion is estimated to be an average of around 4.9 billion m3/MWh. Jakarta itself has a carbon footprint of 25,755 tons of CO2 and produces external cost of US 3,249,506. This study highlights the urgency of reducing carbon emissions through technological innovation, strengthened energy policies and enhanced public energy literacy, with positioning cities as key drivers of the transition toward cleaner energy systems.